Molecular Cytogenetic Identification of a New Wheat-Rye 6R Addition Line and Physical Localization of Its Powdery Mildew Resistance Gene - Han, Guohao; Yan, Hanwen; Wang, Jing; Cao, Lijun; Liu, Shiyu; Li, Xiuquan; Zhou, Yilin; Fan, Jieru; Li, Lihui; An, Diaoguo (Frontiers in Plant Science, 2022)
Rye (Secale cereale L.), a naturally cross-pollinating relative of wheat, is a tertiary gene donor and of substantial value in wheat improvement. Wheat powdery mildew is caused by Blumeria graminis f. sp. tritici (Bgt), which seriously affects yield and quality worldwide. Identifying and transferring new, effective resistance genes against powdery mildew from rye is important for wheat breeding. The current study developed a wheat-rye line YT2 resistant to powdery mildew by crossing, backcrossing, and self-pollination for multiple generations between octoploid triticale 09R2-100 and common wheat cultivar Shixin 616. YT2 was confirmed to be a 6R disomic addition and T1RS·1BL translocation line by genomic in situ hybridization (GISH), multicolor fluorescence in situ hybridization (mc-FISH), multicolor GISH (mc-GISH), and molecular marker analyses. Disease responses to different Bgt isolates and genetic analysis showed that the powdery mildew resistance gene of YT2 was derived from the rye chromosome 6R of 09R2-100, which differed from the previously reported Pm genes from rye including Pm20 on 6RL. Resistance phenotype of different translocation lines and deletion lines derived from YT2 combined with newly developed 6RL-specific markers analysis suggested that the powdery mildew resistance gene of YT2 was localized to the region in chromosome 6RL: 890.09-967.51 Mb, and flanked by markers XM189 and X4M19, corresponding to the reference genome of Weining rye. Therefore, YT2 could be used as a promising bridging parent for wheat disease resistance improvement.